Theory in Hospitality, Tourism, and Leisure Studies - Smith, Stephen L. J.; Xiao, Honggen; Nunkoo, Robin; Tukamushaba, Eddy K. (Journal of hospitality marketing & management, 2013)
The term theory is used with diverse meanings, resulting in miscommunication and misunderstanding. This article examines how theory, as a word, is used in three leading journals in each of hospitality, tourism, and leisure studies fields over a 20-year period. Utilizing an iterative and comparative hierarchical coding, seven different forms of theory and trends in their usage by scholars over the 20 years are identified. Among the notable trends are: (a) a marked increase in the appearance of “theory” (as a word) and its variants over the years; (b) the virtual disappearance of natural science-type theory in the three fields; and (c) a dramatic rise in the use of theory as an analogy rather than as a substantive term. Implications and limitations of the study are also discussed
Keywords: theory; tourism research; hospitality research